The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2020
DOI: 10.1124/pharmrev.120.000056
|View full text |Cite
|
Sign up to set email alerts
|

Psychedelics in Psychiatry: Neuroplastic, Immunomodulatory, and Neurotransmitter Mechanisms

Abstract: Mounting evidence suggests safety and efficacy of psychedelic compounds as potential novel therapeutics in psychiatry. Ketamine has been approved by the Food and Drug Administration in a new class of antidepressants, and 3,4-methylenedioxymethamphetamine (MDMA) is undergoing phase III clinical trials for post-traumatic stress disorder. Psilocybin and lysergic acid diethylamide (LSD) are being investigated in several phase II and phase I clinical trials. Hence, the concept of psychedelics as therapeutics may be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
107
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 130 publications
(138 citation statements)
references
References 1,090 publications
(1,491 reference statements)
1
107
0
2
Order By: Relevance
“…Given the possibility that psychiatry may encounter the prospect of psychedelic therapy in the near future [ 4 , 14 ], it would be interesting to survey Irish psychiatrists’ and psychotherapists attitudes to the evolving field of translational psychedelic science, especially considering the previous contentious relationship between psychiatry and psychedelic therapy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Given the possibility that psychiatry may encounter the prospect of psychedelic therapy in the near future [ 4 , 14 ], it would be interesting to survey Irish psychiatrists’ and psychotherapists attitudes to the evolving field of translational psychedelic science, especially considering the previous contentious relationship between psychiatry and psychedelic therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Preliminary clinical evidence suggests that the synergistic combination of psychedelic compounds with psychological support may improve outcomes in major depressive disorder (MDD) [ 3 , 4 ], treatment-resistant depression (TRD) [ 5 , 6 ], and addiction disorders [ 7 10 ]. Exploratory studies suggest potential benefits of psilocybin therapy in OCD [ 11 ], eating disorders [ 12 ], and migraine suppression [ 13 ], with ongoing clinical trials of psychedelic therapy in MDD, TRD, bipolar disorder type II depression, anxiety, alcohol use disorder, smoking cessation, cocaine addiction, anorexia nervosa, depression with mild cognitive impairment, OCD, and various types of headaches [ 14 ]. Results from ongoing well-powered double-blind randomized controlled trials (RCTs) will determine whether psychedelic therapy translates into clinical benefits for non-psychotic disorders in clinical psychiatry.…”
Section: Introductionmentioning
confidence: 99%
“…All these psychoactive drugs can cause subjective changes in perception, thought, emotion, and consciousness, although with a different mechanism. From preclinical studies, it is clear that the mechanism of hallucinogens is more complex than thought before since their effects on the 5-HT and glutamatergic system as well as their capacity to modulate transcriptional mechanisms seem to emerge very clearly (for review, see Inserra et al, 2021). Importantly, clinical studies have demonstrated the effects of ketamine in treatment-resistant MDD (Marcantoni et al, 2020).…”
Section: Mdma In Clinical Studiesmentioning
confidence: 99%
“…The therapeutic and pro-neuroplastic effects of psychedelics may also be linked to their anti-inflammatory action ( Inserra et al. , 2021 ).…”
Section: Stress and Inflammationmentioning
confidence: 99%